2019
DOI: 10.3390/metabo9020024
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Alterations in Male-Sterile Potato as Compared to Male-Fertile

Abstract: The common potato, Solanum tuberosum L., is the fourth most important agricultural crop worldwide. Until recently, vegetative propagation by tubers has been the main method of potato cultivation. A shift of interest to sexual potato reproduction by true botanical seeds is due to the appearance of a new hybrid seed breeding strategy whose successful application for many crop species has been supported by male sterility. This investigation was focused on the study of differences in the metabolite profiles of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 62 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…Although metabolites during flower, anther, and pollen development in rice [18], tomato [23], wheat [27], and pear [28] have been reported, changes in metabolites associated with pollen abortion in CMS plant (except cotton and potato CMS) is limited [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although metabolites during flower, anther, and pollen development in rice [18], tomato [23], wheat [27], and pear [28] have been reported, changes in metabolites associated with pollen abortion in CMS plant (except cotton and potato CMS) is limited [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, virtually all studied cultivars and breeding clones with the cytoplasm of another wild Mexican species S. stoloniferum can participate in crosses only as female parents (Ross, 1986;Lössl et al, 2000;Song, Schwarzfischer, 2008), because they manifest tetrad sterility (tetrads do not disintegrate in the end of microsporogenesis, and over the entire process of subsequent microgametogenesis microspores remain united into 'permanent tetrads'). Using the method of metabolic profiling on anthers, it has been shown that tetrad sterility is associated with an abrupt disorder of the carbonic exchange in anthers, mainly as far as the polysaccharide spectrum is concerned, and the metabolism of amino and fatty acids (Shishova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this mutant, proper degradation of the cell wall of the PMC after meiosis and subsequent segregation of microspores fail [ 53 , 56 ]. Shishova et al [ 57 ] detected metabolic changes in anthers in T-CMS potato varieties compared with normal pollen-producing varieties. Therefore, it can be assumed that the transcripts of the causal gene for CMS accumulate in the tapetal tissues and PMCs and suppress pollen development.…”
Section: Discussionmentioning
confidence: 99%